2013
DOI: 10.1111/dsu.12242
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Carbon Dioxide Laser Improves Nodular Basal Cell Carcinoma Treatment with Photodynamic Therapy with Methyl 5-Aminolevulinate

Abstract: Fractional laser pretreatment increases the fluorescence and clinical effectiveness of ALA-PDT for the treatment of nBCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 27 publications
0
45
0
2
Order By: Relevance
“…Another study looked at 56 nodular BCCs each of which was ablated using a gallium arsenide 980-nm diode laser under ultrasound control [26]. Three weeks later, half of each BCC then received CO 2 -AFXL, the other half curettage immediately prior to treatment with ALA-PDT.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…Another study looked at 56 nodular BCCs each of which was ablated using a gallium arsenide 980-nm diode laser under ultrasound control [26]. Three weeks later, half of each BCC then received CO 2 -AFXL, the other half curettage immediately prior to treatment with ALA-PDT.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%
“…It is well known that pretreatment of skin with ablative fractional laser (AFL) enhances the uptake and aids topically applied photosensitizer precursors to distribute into skin layers [1][2][3][4][5]. In vivo animal studies and clinical studies have confirmed that AFL pretreatment successfully facilitates an intensified PDT response [1,[6][7][8][9][10][11][12][13][14][15]. Internationally, AFL-mediated PDT is gaining clinical acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…This finding indicates that low channel densities should be sufficient to facilitate uniform accumulation of PpIX. However, clinical studies on AFL-mediated PDT have applied a wide range of densities from 5% to 22% [6,7,[10][11][12][13]15,22]. Limited information is available on pharmacokinetics for MAL uptake and biodistribution in AFL pretreated skin.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ALA-PDT could not be used as a treatment for nodular basal cell carcinoma because these tumors were thicker than 2 mm. However, Lippert et al [14] showed that ALA-PDT with ablative laser therapy could overcome the limit caused by tumor thickness in patients with nBCC as the increased penetration allowed ALA to reach deep enough into the tumor layers. Yin et al [15] evaluated the effects of erbium: yttrium-aluminum-garnet (Er:YAG) ablative fractional laser resurfacing for treatment of severe acne.…”
Section: Improvements In Ala Penetrationmentioning
confidence: 99%